Evidence for the economic impacts of Eucalyptus and Subabul-based agroforestry in Andhra Pradesh and Telangana - Soam, Sudhir Kumar; P, Venkatesan; N, Sivaramane; P D, Sreekanth; S, Rakesh; Tamak, Jagdish; A, Arunachalam; Pandey, Suneel; Ch, Srinivasarao (Indian Journal of Agroforestry, 2023)
Profitability, risk analysis and farmers perception were worked out for Eucalyptus and Subabul based agroforestry growers in Telangana and Andhra Pradesh. A total of 465 farmers were considered under survey in both states. Establishment cost of Subabul was considerably lesser but the maintenance cost was almost similar as compared to Eucalyptus. Gross returns of Subabul were better than Eucalyptus. Major constraints (as recorded in both states) in tree cultivation were: Price fluctuations>water problem>marketing>labour problem. This research helps the stakeholders such as farmers, researchers, government and non-government organizations and policymakers in decision making to promote agroforestry in India.